Factors Considered for Outsourcing Decision of Support Services by the National Health Service, United Kingdom - Ab Rahim, Norbaya; Baldry, David; Nordin, Muhamad Saiful Alizan; Ab Majid, Rohayu; Bakri, Anis Sazira (International Journal of Sustainable Construction Engineering and Technology, 2023)
Outsourcing of support services has been in practice for decades. It was once used as a means of reducing costs and has now evolved and is being considered strategically by organisations. Not only is outsourcing prevalent in the private sector, it is also growing in the public sector including public healthcare. Outsourcing also allows for the implementation of new technologies, processes, and strategies that would not otherwise be available. Despite the increasing prevalence of outsourcing of support services in the National Health Service (NHS) of the United Kingdom, there is a lack of research into the factors that should be considered when evaluating the potential of outsourcing. Therefore, this research seeks to evaluate the factors to be considered in the decision to outsource the support services in the NHS. This research has taken a qualitative approach with a multiple-case study concept adopted as the research strategy. Three (3) NHS Trusts have been identified with 21 respondents from senior management and middle management levels. The main data collection was through face-to-face semi-structured interviews. The findings revealed the factors to be considered in outsourcing decisions for the NHS Trusts and are grouped into seven (7) themes. These are namely the Environmental Factor, Financial Factor, Legal Factor, Risks Factor, Service Provider Factor, Social Factor, and Trust Factor. This research acknowledges that there is a need for Trusts to understand comprehensively the concept of outsourcing, and the motivation for them to go into outsourcing. In addition, the Trusts also need to acknowledge the factors that they should consider prior to deciding on outsourcing.